Cluster analysis of prolonged grief, posttraumatic stress, and depression symptoms in bereaved asylum seekers and refugees - Comteße, Hannah; Edelhoff, Hannah; Rosner, Rita; Lechner-Meichsner, Franziska (European journal of psychotraumatology, 2024)
Background: Refugees and asylum seekers (ASRs) are frequently exposed to loss in addition to a variety of other stressors and often display high levels of various psychological symptoms. Objective: The study aimed to primarily determine clusters of prolonged grief disorder (PGD), posttraumatic stress disorder (PTSD), and depression symptoms in bereaved ASRs and secondly identify predictors of cluster membership. Sociodemographic - and flight-related variables were investigated in exploratory analyses. Method: ASRs in Germany (N = 92) with interpersonal loss exposure, i.e. at least one missing or deceased relative or friend, were assessed with interview-based questionnaires for PGD, PTSD, and depressive symptoms. We used k-means cluster analysis to distinguish symptom profiles and logistic regression analyses to identify predictors of cluster membership. Results: We found a three-cluster-solution. The PGD-cluster (30%) was characterised predominantly by PGD symptoms, while the PGD/PTSD-cluster (32%) had high PGD and PTSD and moderate depressive symptoms. The resilient cluster (38%) showed low symptoms overall. insecure residence status predicted membership in the PGD and PGD/PTSD clusters relative to the resilient cluster, whilst higher attachment anxiety predicted membership in the PGD/PTSD cluster relative to the other clusters. Explorative analysis revealed duration of stay as a significant predictor. Conclusion: Findings can extend the current knowledge about different symptom profiles among bereaved ASRs in Europe. Insights to attachment - and migration-related variables distinguishing between these profiles offer starting points for interventions. Bereaved asylum seekers and refugees in Germany can be grouped into three symptom clusters: (1) predominantly prolonged grief, (2) high prolonged grief, high posttraumatic stress, and moderate depressive symptoms, and (3) low symptom load.Attachment - and migration-related variables (i.e. residence status, duration of stay, and attachment anxiety) distinguish between cluster membership.Results highlight the importance of attending to profiles and not only single categories of symptoms and attachment features in bereaved asylum seekers and refugees. Bereaved asylum seekers and refugees in Germany can be grouped into three symptom clusters: (1) predominantly prolonged grief, (2) high prolonged grief, high posttraumatic stress, and moderate depressive symptoms, and (3) low symptom load. Attachment - and migration-related variables (i.e. residence status, duration of stay, and attachment anxiety) distinguish between cluster membership. Results highlight the importance of attending to profiles and not only single categories of symptoms and attachment features in bereaved asylum seekers and refugees.
Gesehen am 10.03.2025